1991
DOI: 10.1007/bf00197948
|View full text |Cite
|
Sign up to set email alerts
|

Time-course study of the accumulation of hydroxyproline-rich glycoproteins in root cells of susceptible and resistant tomato plants infected by Fusarium oxysporum f. sp. radicis-lycopersici

Abstract: The accumulation of hydroxyproline-rich glycoproteins (HRGPs) in cell walls of dicotyledonous plants is thought to be involved in the defense response to pathogens. An antiserum raised against deglycosylated HRGPs from melon was used for studying the subcellular localization of these glycoproteins in susceptible and resistant tomato (Lycopersicon esculentum Mill.) root tissues infected by Fusarium oxysporum f.sp. radicis-lycopersici. A time-course of HRGP accumulation revealed that these glycoproteins increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…These results confirm and extend several previous studies which have reported more rapid increases in cell wall HRGPs in resistant than in susceptible genotypes in different host-pathogen interactions such as the cucumber Á Cladosporium cucumerinum (Hammerschmidt et al 1984), the tomato Á Fusarium oxysporum f. sp. radicis-lycopersici (Benhamou et al 1991), the tobacco Á Erysiphe cichoracearum (Raggi 2000), the wheat Á F. culmorum (Kang and Buchenauer 2003) and the pearl millet Á Sclerospora graminicola (Shailasree et al 2004) interactions. HRGPs were extracted from cell walls by a harsher treatment using a combination of acid and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm and extend several previous studies which have reported more rapid increases in cell wall HRGPs in resistant than in susceptible genotypes in different host-pathogen interactions such as the cucumber Á Cladosporium cucumerinum (Hammerschmidt et al 1984), the tomato Á Fusarium oxysporum f. sp. radicis-lycopersici (Benhamou et al 1991), the tobacco Á Erysiphe cichoracearum (Raggi 2000), the wheat Á F. culmorum (Kang and Buchenauer 2003) and the pearl millet Á Sclerospora graminicola (Shailasree et al 2004) interactions. HRGPs were extracted from cell walls by a harsher treatment using a combination of acid and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Benhamou et al (1991) consider that the major epitopes recognized by the HRGP 2b antiserum are on the polypeptide moiety of the molecule. The accumulation of HRGPs within deposits and cell walls prior to the detection of phenolic compounds at these sites is consistent with their proposed role in providing nucleation sites for lignin-like polymer deposition (Whitmore, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Localized induction of extensin proteins has been documented in several compatible and incompatible plant-fungi (Benhamou et al, 1991) or plant-bacteria (Mazau and Esquerre-Tugaye, 1986;O'Connell et al, 1990) interactions, both in regions of contact with the pathogen and in the neighboring intercellular space. We thus expected to observe a similar phenomenon upon nematode infection.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas significant efforts have been devoted to studying HRGPs in plant-fungus (Benhamou et al, 1990a(Benhamou et al, , 1991, plantbacteria (OConnell et al, 1990), and plant-virus (Benhamou et al, 1990b) interactions, to our knowledge, no work has been reported on HRGPs in plant-nematode interactions.…”
Section: Introductionmentioning
confidence: 99%